انشغالات الأقلام النسائية الصحفية في الوطن العربي دراسة تحليلية لجريدة الفجر الجزائرية، جريدة الأهرام المصرية، جريدة الرياض السعودية - بوسنان, رقية (University of Eloued جامعة الوادي, 2018)
ركز البحث على الأقلام الصحفية النسائية التي تعالج مختلف القضايا والحوادث التي تسود المجتمعات المختلفة في في البيئة والجغرافيا والعادات والتقاليد، وقد تمكنت بعض الأقلام فعلا من أن تبثت فاعليتها عن طريق طرح انشغالاتها السياسية والاجتماعية والثقافية والإبداعية، وبالرغم من الاختلاف السائد على مستوى الانشغالات المتضمنة في الصحف الثلاث إلا أنها توحي بان المرأة تسعى جاهدة إلى طرحه بنوع من الاحترافية والتخصص، وبهذا تضع المرأة بصماتها في عالم الصحافة المكتوبة لتؤكد على حضورها الاجتماعي والثقافي والسياسي والأكاديمي بالرغم من المشكلات التي تعترضها في المحيطين الداخلي و الخارجي، وتحرص كل من الأقلام النسائية على العمل الصحفي وفقا للقوانين المشرعة في كل بلد تنتمي إليه. Abstract The importance of the research is stated on its focuses on women's journalistic pens that fixed different Issues and accidents that are spread in different societies, environment, geographic, and traditions. and some of those women pens have actually been able to broadcast their effectiveness by raising their political, social, cultural and creative concerns. In spite of the difference in the level of concerns included in the three newspapers, it suggests that women strive to offer them with a kind of professionalism and specialization, but it shows and explains that women are working hardly to ask and research with huge abilities and professional. and because that the women put their path in written journal world to convince their social, cultural political and academicals existence even with all the problems that faced on the external and internal environment and each of those women pens are care and respect the journal working depending on the legal low of every country belong to.
The concerns of the feminist journalistic pens in the Arab world An analytical study of Al-Fajr Algeria newspaper Al-Ahram Egypt newspaper, Al-Riyadh Saudi Arabia newspaper
مجلة البحوث والدراسات المجلد 15 العدد01 جامعة الوادي
Keywords: الانشغال، الأقلام النسائية، الصحافة العربية.; preoccupation; female pens; Arabic press.